THE IMPORTANCE OF DEVELOPING DIGITAL SERVICES IN RURAL AREAS OF THE REGION - Taylakova, Dilafruz Baymamatovna (THE INNOVATION ECONOMY, 2026)
This article argues that the development of digital services in rural areas of the region is one of the important factors in ensuring sustainable socio-economic development of rural areas of the region. The introduction of banking and finance, trade, education, medicine, public services and agro-service systems based on digital technologies in rural areas of the region will reduce economic disparities between regions, expand the access of the rural population of the region to modern services, and provide scientific proposals to reduce transaction costs